Influence of Axial Clearance between Bottom of Cartridge Case and Front Surface of Breech To Primary Load of Gun (Advances in Military Technology, 2022)
The article deals with influence of breech clearance to primary loading of gun breech. Theoretical solution was verified by experiment.
Keywords: Force to breech; breech clearance